Identification of resistance gene analogs of the NBS-LRR family through transcriptome probing and in silico prediction of the expressome of Dalbergia sissoo under dieback disease stress - Ijaz, Siddra; Haq, Imran Ul; Khan, Iqrar Ahmad; Ali, Hayssam M.; Kaur, Sukhwinder; Razzaq, Hafiza Arooj (Frontiers in Genetics, 2022)
Dalbergia sissoo is an important timber tree, and dieback disease poses a dire threat to it towards extinction. The genomic record of D. sissoo is not available yet on any database; that is why it is challenging to probe the genetic elements involved in stress resistance. Hence, we attempted to unlock the genetics involved in dieback resistance through probing the NBS-LRR family linked with mostly disease resistance in plants. We analyzed the transcriptome of D. sissoo under dieback challenge through DOP-rtPCR analysis using degenerate primers from conserved regions of NBS domain encoded gene sequences. The differentially expressed gene sequences were sequenced and in silico characterized for predicting expressome that contributes resistance to D. sissoo against dieback. The molecular and bioinformatic analyses predicted the presence of motifs including ATP/GTP-binding site motif A (P-loop NTPase domain), GLPL domain, Casein kinase II phosphorylation site, and N-myristoylation site, etc. that are the attributes of proteins encoded by disease resistance genes. The physicochemical characteristics of identified resistance genes analogs, subcellular localization, predicted protein fingerprints, in silico functional annotation, and predicted protein structure proved their role in disease and stress resistance.